Forage improvement - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
Se presentan aspectos sobre el mejoramiento de Stylosanthes capitata, S. guianensis, Centrosema pubescens, Leucaena leucocephala, Andropogon gayanus, Panicum maximum y Brachiaria spp. (Herbage Abstracts-CIAT)